Study on Electromagnetic Interference of high-speed railway EMU - LIU Jin-jiang; CHENG Qiang; CHENG Ning (Institute of Advanced Engineering and Science, 2014)
Electromagnetic radiation generated by pantograph-catenaries detachment is one of the inevitable problems with the development of high-speed railway this paper is focusing on the generating mechanism and characteristics of electromagnetic noise caused by pantograph-catenaries system. Based on previous research, we build an integrated model of catenaries and locomotive system, and study the electromagnetic disturbance characteristics using software FEKO． The simulation experiment results in the end can not only provide accurate data, but also give a more intuitive understanding of electromagnetic field distribution and attenuation characteristics generated by pantograph detachment. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3899